Percutaneous nephrolithotomy (PCNL) a critical review. (December 2016) - Ganpule, Arvind P.; Vijayakumar, Mohankumar; Malpani, Ankur; Desai, Mahesh R.
Abstract: Introduction: Percutaneous nephrolithotomy (PCNL) is the preferred treatment of choice for renal calculi. PCNL has evolved remarkably since the eighties when it was first described. Approach: Approach might be by either supine or prone and the access is made with the help of either fluoroscopy or ultrasound. Recently endoscopy guided puncture has also been described. Miniaturization: Traditionally the tract size for PCNL used to be 30Fr. Even though the stone clearance rate was good there were complications such as bleeding With the advent of excellent optics and advances in stone fragmentation the tract size has reduced to a great extent which has reduced the complications without compromising the stone clearance. Complications: The complications related to access might be injury to pleura, and other visceral organs. The other complications are bleeding, infection and incomplete stone clearance. Conclusion: PCNL has emerged as most efficient procedure among these approaches to stone removal, though not devoid of complications and requirement for skills. The drive for minimal invasive approach should not compromise stone clearance, latter being the core principle of endourology. In skilled hands PCNL is the answer to stone questions we as urologist face day to day. though which form of PCNL is to be chosen depends on surgeons skill level and discretion. Highlights: Percutaneous nephrolithotomy (PCNL) is the preferred treatment of choice for renal calculi. The usual indications for PCNL are stones larger than 20 mm, staghorn, partial staghorn calculi. The reduction in tract size in PCNl has reduced the complications without affecting stone clearance rate.